Profitability and zakat payment: The role of firm size - Mais, Rimi Gusliana; Hastuti, Dian Dwi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This study aims to investigate the impact of two profitability proxies, Return on Asset (ROA) and Return on Equity (ROE), on zakat payments in Islamic Commercial Banks between 2016 and 2020. Firm size will be examined as a moderating variable. The research method used is a descriptive quantitative approach. The population of this study consists of Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) during the designated period, 2016-2020. Nine banks were selected using purposive sampling, resulting in 45 observations. Multiple linear regression analysis was performed using the EVIEWS 12 application tool to test the research hypotheses. The findings revealed that ROA and ROE positively affected company zakat payments. However, firm size did not moderate the effect of ROA on zakat payments. In contrast, it did moderate the impact of ROE on zakat payments